The Finnish diabetes risk score predicts impaired glucose tolerance in a heart failure population. (22nd September 2015) - Chacko, S; Gow, J; Bowell, S; Mamas, MA; Neyses, L
Abstract : Introduction: The prevalence of diabetes mellitus (DM) in patients with heart failure has been reported at between 16% and 50% with a prevalence of 27% in the recent EuroHeart failure survey. Analysis of the recent CHARM programme has demonstrated that presence of DM is associated with an adverse outcome in patients with heart failure with both preserved and impaired left ventricular systolic function. What is not clear is the prevalence of impaired glucose tolerance (IGT) in patients with heart failure. A recent study (Berry et al, Heart 2007) has demonstrated that close to 15% of heart failure patients presenting with acute heart failure have IGT and that is a strong independent predictor of mortality. Methods: A group of specialist breast cancer oncologists, cardiologists and a cardiovascular lead general practitioner reviewed the current trastuzumab guidelines and all published safety data. Applying data from the clinical trials, the mechanisms of the cardiac effects of trastuzumab and evidence-based cardiology practice, the group drafted interventional guidelines that promote a proactive approach to identifying and managing cardiac events in patients with breast cancer who are planned to receive standard cytotoxic chemotherapy and trastuzumab. Results: The key recommendations include proactive monitoring and cardiac assessment before chemotherapy (not current routine practice in the UK), before and during trastuzumab therapy with simplified assessment criteria. Rather than the purely observational approach employed in trastuzumab clinical trials, a pharmacological intervention strategy with ACE inhibitors to manage hypertension and reductions in ejection fraction before and during treatment is introduced. Simple rules for starting, interrupting and discontinuing trastuzumab and clear recommendations on when cardiology consultation is appropriate for breast cancer patients are suggested (see figs 1 and 2). Methods: We have studied the prevalence of IGT prospectively in 40 non-diabetic consecutive patients attending the outpatient heart failure clinic at Manchester Heart Centre by means of an oral glucose tolerance test (OGTT). Furthermore, using the Finnish diabetes risk score (FINDRISC), a questionnaire-based risk score validated for use as a screening tool to identify asymptomatic high-risk patients for the development of DM and for the early detection of DM, we have studied its feasibility as a screening tool for undetected DM and IGT in this cohort. Results: Patient demographics are presented in table 1. Of the 40 patients undergoing OGTT, a total of 12/40 (30%) had IGT as defined by WHO criteria and four (10%) had DM. Using a cut-off FINDRISC score of 12 or more, which represents a moderate risk of DM, data obtained from OGTT are presented in table 2, in which a sensitivity of 87.5% and specificity of 83.33% were calculated for the detection of IGT and DM as diagnosed by OGTT. Conclusion: Using OGTT we have found a high prevalence (40%) of IGT and undetected DM in patients not thought to have diabetes in an outpatient heart failure cohort. Furthermore, in our study population the FINDRISC screening tool has high sensitivity and specificity for detecting DM and IGT and it is a feasible and non-invasive tool for screening high-risk individuals in the outpatient setting.